Comparisons of tri-ponderal mass index and body mass index in discriminating hypertension at three separate visits in adolescents: A retrospective cohort study - Hu, Jia; Zhong, Yi; Ge, WenXin; Lv, Huiling; Ding, Ziyao; Han, Di; Hai, Bo; Shen, Hui; Yin, Jieyun; Gu, Aihua; Yang, Haibing (Frontiers in Nutrition, 2022)
Objective: To estimate whether the new obesity indicator tri-ponderal mass index (TMI) has a better capacity to predict adolescent hypertension (HTN) and HTN subtypes at three separate blood pressure (BP) visits than the conventionally used body mass index (BMI). Methods: A total of 36,950 adolescents who had initial normal BP from 2012 to 2019 were included in Suzhou, China. HTN was defined as having three separate visits of elevated BP in 2020. The area under the receiver-operating characteristic curve (AUC), false-positive rate (FPR), false-negative rate (FNR), total misclassification rates, net reclassification improvement (NRI), and integrated discrimination improvement (IDI) were calculated to compare the discriminative ability of HTN between BMI and TMI. Results: TMI had better predictive abilities than BMI among all of the participants when predicting HTN (difference in AUC = 0.019, 95% CI = 0.007-0.031; NRI = 0.067, 95% CI = 0.008-0.127) and isolated systolic hypertension (difference in AUC = 0.021, 95% CI = 0.005-0.036; NRI = 0.106, 95% CI = 0.029-0.183). The difference in prediction abilities between BMI and TMI was more obvious in the subgroup of age ≥ 16. Also, TMI outperformed BMI in predicting adolescent HTN in girls but not in boys. Conclusions: Compared with BMI, TMI may have a better predictive capacity for HTN, particularly in girls and older adolescents. TMI has the potential to be used as an effective predictor for HTN in clinic practice. Further studies are needed to verify the utility of TMI.